Immunohistochemical expression of plasminogen activator inhibitor-1 in subcutaneous versus omental adipose tissue in patients after elective abdominal surgery - BOZKURTLAR, EMİNE (My University, 2019)
Plasminogen activator inhibitor-1 (PAI-1) is a biomarker of thrombosis. Adipose and vascular tissues are among the major sources of PAI-1 production. Previous studies indicated that fat deposits mediate increased cardiovascular risk among obese individuals. We investigated the immunohistochemical (IHC) expression of PAI-1 in adipose and vascular tissues from the omentum and the subcutaneous tissue. The pathology samples were selected from 37 random patients who underwent elective abdominal surgery between 2008-2009. PAI-1 expression was semi-quantitatively scored and compared between the groups. Significant differences were noted in the IHC expression of PAI-1 between the omental and the subcutaneous adipose tissues (1.1 ± 0.8 versus 0.8 ± 0.6, respectively (p=0.05)). Adipose tissue displayed higher IHC expression of PAI-1 compared to vascular wall tissue in both omentum and subcutaneous sections (1.1 ± 0.8 versus 0.5 ± 0.9 (p=0.004), and 0.8 ± 0.6 versus 0.4 ± 0.6 (p=0.003), respectively). In conclusion, our study compared PAI-1 expression in the omentum versus the subcutaneous tissue and adipose versus vascular tissues. IHC expression of PAI-1 level was significantly higher in the omental adipose tissue compared to the subcutaneous adipose tissue. Adipose tissue displayed significantly higher PAI-1 expression than vascular tissue. The study elucidates the biological differences of adipose and vascular tissue from subcutaneous versus omental sections.
Keywords: Immunohistochemistry; Adipose Tissue; Plasminogen Activator Inhibitor-1